2020
DOI: 10.1155/2020/5639284
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Parameters Related to Vision Impairment in Patients with Diabetic Macular Edema: A Quantitative Correlation Analysis

Abstract: Purpose. To quantitatively explore the correlation between optical coherence tomography (OCT) parameters and vision impairment in patients with diabetic macular edema (DME). Methods. This study was a retrospective observational case series. One-hundred eyes from 66 patients with DME were retrospectively included. OCT parameters, including central macular thickness (CMT), height of intraretinal cystoid, subretinal fluid and sponge-like retinal swelling, density of hyperreflective foci (HRF), and integrity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…In eyes with DME, HRF located in the outer retinal layers have been strongly associated with worse visual prognosis, disruption of the ELM, photoreceptor loss, and worse prognosis after vitrectomy [6,29,40,41]. An alternative method of studying the integrity of the photoreceptor-RPE complex in the so-called "parallelism" supported that HRF in the outer retinal layers affects photoreceptor layer continuity.…”
Section: Clinical and Prognostic Implications Of Hyperreflective Foci In Diabetic Macular Edemamentioning
confidence: 99%
“…In eyes with DME, HRF located in the outer retinal layers have been strongly associated with worse visual prognosis, disruption of the ELM, photoreceptor loss, and worse prognosis after vitrectomy [6,29,40,41]. An alternative method of studying the integrity of the photoreceptor-RPE complex in the so-called "parallelism" supported that HRF in the outer retinal layers affects photoreceptor layer continuity.…”
Section: Clinical and Prognostic Implications Of Hyperreflective Foci In Diabetic Macular Edemamentioning
confidence: 99%
“…In our study, more than one third of patients experienced hypertension and hyperlipemia, with the univariate analysis and final multivariate analysis, our data demonstrated that hypertension and hyperlipemia impaired the effect of anti-VEGF agents and predicted the poor prognosis of RVO. Additionally, several studies have revealed OCT parameters are related to visual acuity in vascular eye diseases ( Li et al, 2020 ; Sun et al, 2014 ). For example, a relationship between the pre-treatment status of the ELM and post-treatment visual outcome has been described for eye diseases ( Liu et al, 2018 ; Theodossiadis et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar progress has been made in patients with DME because OCT has been able to identify various pathologies in these patients, such as CMT, HF, SF, EZ/ELM irregularity and DRIL, and these ndings have begun to clarify the pathogenesis and prognosis of the disease. A large number of studies have been conducted on DME patients receiving anti-VEGF injections, and it has been con rmed that the microstructural changes seen at the baseline by OCT scans can predict the treatment response [14,10,15]. The TCED-HFV classi cation, as a non-invasive diagnostic method, had shown its potential for early diagnosis of DME and could quantitatively response the therapeutic effect to anti-VEGF treatment.…”
Section: Discussion/conclusionmentioning
confidence: 99%